A Conceptual Review of the Challenges of Effective Tax Collection from the Informal Sector in Kano, Nigeria (Journal of Business Management and Accounting, 2019)
The informal sector is often referred to as unregulated financial undertakings and poses a serious challenge to government in relation to tax revenue collection. The main issue of concern is why a wide gap exists between the actual tax collections from the informal sector and the potential tax that should be collected. Thus, the main aim of this study is to identify and examine some of the challenges militating against effective tax collection from the informal sector in Kano State, Nigeria. The paper is literature based, as such, it critically examines current literature on tax collection. It was discovered that issues such as reliance on cash based transactions, absence of required records and weak tax laws are some of the challenges preventing effective tax collection from the informal sector. It is therefore recommended that tax collection from the informal sector could be enhanced when government educates the informal operators, strengthens tax laws, emphasize on adequate records keeping and simplify the formalization procedures.